(untitled) - Tolkien, J.R.R (New York, 1987)
To protect a magic ring, Frodo, the hobbit, must undertake a long and dangerous journey
Keywords: Tiểu thuyết viễn tưởng Anh,Fantasy fiction, English,Wizards,Magicians,Phù Thủy,Pháp sư; Drama,Drama,Phim,Phim